Decorative Decorations in Gold Thread Shown on Aisles and Women's Bride Clothes in Naras, Pariaman City - Dilla Annisa Putri; Yuliarma Yuliarma (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
An overview of the characteristics of motif design, including motif design, decorative patterns, placement of motifs, color combinations, and gold thread embroidery techniques on wedding dresses and aisles in Naras Kota Pariaman, is presented in this study. The method used is descriptive qualitative with the main data needed in the form of primary data and secondary data. Data were collected through observation, interview, and documentation techniques. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. To get the validity of the data obtained through triangulation. The results of this study are 1) The design characteristics of the motifs used in gold thread embroidery products sourced from nature (naturalists) are clam flowers which are stilasid into ornamental shapes, other motifs used are roses, jasmine flowers, orchids, kaladi leaves, sunflowers, kaluak paku, animal motifs such as lions and peacocks. The decorative patterns used include standing edge decorative patterns, climbing edge decorative patterns, roadside decorative patterns, hanging edge decorative patterns, rectangular fillings, triangular field fillings, and sowing patterns. The placement of motifs on the wedding dress includes the neck, sleeves, bottom of the shirt, the back of the shirt, tokah, while on the aisle the placement of gold thread embroidery motifs on banta gadang, lansia, tabia, lidah-lidah, ondas-ondas, angkin, and Dalamak. 2) The color combination in this embroidery product uses a primary base color, and a combination of neutral colors, monochromatic color combinations, and complementary color combinations. 3) The gold thread embroidery technique used is first to prepare the tools and materials, make the motif on paper/directly on the cloth, trace the motif, embroider the motif using gold or silver thread and then wrap it with ordinary thread using the sewing technique , then done. The materials used for wedding dresses are satin, velvet, and bridal, while for the aisle the materials are satin and velvet used